Hubungan Pemberian MP-ASI Instan dan MP-ASI Tradisional dengan Status Gizi Bayi Usia >6-12 Bulan - Dahrianti, Evi Sri; Herlianty; Bauw, Mira Kohmala; Nurhidaya; Abukasim, Eka Mustika Sari (ProHealth Journal, 2025)
This study aims to identify the provision of instant and traditional MP-ASI and the nutritional status of infants aged >6-12 months who received both types of MP-ASI at the Anggeraja Health Center, Enrekang Regency. This study employs a quantitative descriptive approach with a sample size of 30 respondents, consisting of parents of infants who provide either instant or traditional MP-ASI. Data were collected through interviews and direct observation. Data analysis was performed using frequency distribution and Chi-Square tests to analyze the relationship between the provision of MP-ASI and the nutritional status of the infants. Among the 30 respondents, 63.3% provided instant MP-ASI with a good category, while 76.7% provided traditional MP-ASI with a good category. The nutritional status of infants receiving instant MP-ASI showed that 63.3% had normal nutritional status, and 76.7% of infants receiving traditional MP-ASI had normal nutritional status. The Chi-Square test showed a significant relationship between the provision of MP-ASI and the nutritional status of infants (p-value < 0.05).